2011
DOI: 10.1055/s-0031-1296670
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study with Azelnidipine in Patients with Essential Hypertension

Abstract: A dihydropyridine calcium (Ca) antagonist, azelnidipine (CAS 123524-52-7, Calblock), exhibits hypotensive effects for a prolonged duration, and has been reported to have a strong antiarteriosclerotic action due to its high affinity for vascular tissues and antioxidative action. It has also been reported that azelnidipine does not cause tachycardia associated with the baroreceptor reflex due to vasodilatation. In this study, the antiarteriosclerotic and cardiac hypertrophy-inhibitory effects, and the autonomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 22 publications
1
8
1
Order By: Relevance
“…These results are consistent with previous reports in which azelnidipine decreased clinic-measured HR and 24-hour HR, whereas amlodipine increased both of these parameters, despite similar BP reductions 8,23. It was also reported that, after switching from amlodipine, azelnidipine exhibited hypotensive effects compared with amlodipine, and significantly decreased HR and the total number of extrasystole phases 24. Noradrenaline levels and the LF/HF ratio were significantly decreased, and the washout rate was significantly reduced on 123I-MIBG myocardial scintigraphy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with previous reports in which azelnidipine decreased clinic-measured HR and 24-hour HR, whereas amlodipine increased both of these parameters, despite similar BP reductions 8,23. It was also reported that, after switching from amlodipine, azelnidipine exhibited hypotensive effects compared with amlodipine, and significantly decreased HR and the total number of extrasystole phases 24. Noradrenaline levels and the LF/HF ratio were significantly decreased, and the washout rate was significantly reduced on 123I-MIBG myocardial scintigraphy.…”
Section: Discussionsupporting
confidence: 92%
“…Noradrenaline levels and the LF/HF ratio were significantly decreased, and the washout rate was significantly reduced on 123I-MIBG myocardial scintigraphy. These findings suggest that azelnidipine inhibits the enhancement of sympathetic nervous activity 24. These differences in the effects of azelnidipine and amlodipine can also be explained by the finding that azelnidipine exerts stronger inhibition of sympathetic activity in the vasodilation-induced baroreceptor reflex than does amlodipine 7…”
Section: Discussionmentioning
confidence: 95%
“…Impaired BRS due to modified predominant alpha-sympathetic activity and increased arterial stiffness in the elderly may be a key physiological mechanism of increased ME-Dif [20]. AZ has been shown to ameliorate BRS [13] and to inhibit sympathetic nervous activity via vasodilation-induced baroreceptor reflex [12]. The improvement of the age-related increase in ME-Dif after treatment with AZ as observed in the present study is considered due to these known actions of this agent.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is known that some CCB agents decrease BP very rapidly resulting in enhanced sympathetic activity by baroreceptor reflex and increased pulse rate, conversely, since AZ suppresses sympathetic nervous activity this agent does not induce reflex tachycardia [12]. Thus AZ-induced decrease of pulse rate possibly contributes to improvement of BRS by this agent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation